Critical Involvement of TFIIB in Viral Pathogenesis - O’Brien, Michael J.; Ansari, Athar (Frontiers in Molecular Biosciences, 2021)
Viral infections and the harm they cause to their host are a perpetual threat to living organisms. Pathogenesis and subsequent spread of infection requires replication of the viral genome and expression of structural and non-structural proteins of the virus. Generally, viruses use transcription and translation machinery of the host cell to achieve this objective. The viral genome encodes transcriptional regulators that alter the expression of viral and host genes by manipulating initiation and termination steps of transcription. The regulation of the initiation step is often through interactions of viral factors with gene specific factors as well as general transcription factors. Among the general transcription factors, TFIIB (Transcription Factor IIB) is a frequent target during viral pathogenesis. TFIIB is utilized by a plethora of viruses including human immunodeficiency virus, herpes simplex virus, vaccinia virus, Thogoto virus, hepatitis virus, Epstein-Barr virus and gammaherpesviruses to alter gene expression. A number of viral transcriptional regulators exhibit a direct interaction with host TFIIB in order to accomplish expression of their genes and to repress host transcription. Some viruses have evolved proteins with a three-dimensional structure very similar to TFIIB, demonstrating the importance of TFIIB for viral persistence. Upon viral infection, host transcription is selectively altered with viral transcription benefitting. The nature of viral utilization of TFIIB for expression of its own genes, along with selective repression of host antiviral genes and downregulation of general host transcription, makes TFIIB a potential candidate for antiviral therapies.